1988
DOI: 10.1007/bf02431541
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of clonidine and antidepressant drugs in the mouse forced-swimming test

Abstract: In the mouse forced-swimming model, dose-dependent reversal of immobility was induced by the alpha-agonist clonidine given IP 30 min before testing. In addition, three preferential inhibitors of 5-HT uptake (citalopram, indalpine and fluvoxamine) had similar activity in the dose range 8-16 mg/kg as did the 5-HT1 agonist 8-OH-DPAT (1-4 mg/kg). Pretreatment with alpha-methyl-paratyrosine (100 mg/kg) did not prevent clonidine (1 mg/kg) action, suggesting that there was mediation by alpha post-junctional receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…It is generally accepted that selective inhibitors of serotonin uptake do not show an antidepressant-like activity in the forced swimming test in rats (Borsini, 1995;G6rka et al, 1979;Maj et al, 1982;Porsolt et al, 1978), although some authors described positive effects, especially in mice (Cervo et al, 1991;Nixon et al, 1994;Malinge et al, 1988). The presently obtained results support the above data.…”
Section: Discussionsupporting
confidence: 92%
“…It is generally accepted that selective inhibitors of serotonin uptake do not show an antidepressant-like activity in the forced swimming test in rats (Borsini, 1995;G6rka et al, 1979;Maj et al, 1982;Porsolt et al, 1978), although some authors described positive effects, especially in mice (Cervo et al, 1991;Nixon et al, 1994;Malinge et al, 1988). The presently obtained results support the above data.…”
Section: Discussionsupporting
confidence: 92%
“…Two, 4, and 8 mEq/kg lithium were shown to have a small but significant effect on immobility time, and when the subactive 1 mEq/kg was administered 15 minutes before a subactive dose of the 5HT(1A) agonist gepirone, immobility time was also reduced. This adjunctive effect of lithium, which it shares (though not identically) with clonidine and quinine, has been shown for a number of different kinds of antidepressants, including SSRIs, MAOIs, tricyclic, and atypical antidepressants (Malinge et al, 1988;Bourin et al, 1991;Hascoet et al, 1994;Nixon et al, 1994;Guo et al, 1995;Bourin et al, 1996;Redrobe et al, 1998). This additive mechanism is likely to be mediated at least in part by the serotonergic system, as antidepressants specific for dopaminergic and noradrenergic transmission are not affected by lithium in this model (Nixon et al, 1994).…”
Section: Effect Of Lithium On the Forced Swim Testsupporting
confidence: 65%
“…However, even if a sedative effect is observed in the locomotor-activity measuring device, antidepressant-like activity may be perceived in the FST Malinge et al, 1988). The observed downregulation of a 1 -adrenoceptor in NET À/À mice together with their increased activity in the behavioral tests is an interesting finding, as blockade of a 1 -adrenoceptors by prazosin (Stone and Quartermain, 1999) or terazosin (Stone et al, 2003) has been reported to produce cessation of behavioral activity, also in the TST.…”
Section: Discussionmentioning
confidence: 90%